Transient immune-mediated agranulocytosis following Mycoplasma pneumoniae infection. (18th April 2018) - Barge, Luani; Pahn, Gail; Weber, Nicholas
Abstract : Mycoplasma pneumoniae is a common respiratory pathogen which may cause haematological manifestations including haemolytic anaemia and thrombocytopaenia. Severe neutropaenia is rare with very few cases reported in the literature. An 85-year-old man was transferred to our facility with agranulocytosis in the context of an infective exacerbation of chronic obstructive pulmonary disease with positive serological testing for M. pneumoniae. No alternative infective, autoimmune or lymphoproliferative cause of the neutropaenia was identified. Granulocyte autoantibody testing was performed with a positive result for neutrophil-bound IgG and IgM autoantibodies and significant agglutination reactions. The patient was treated with azithromycin and granulocyte colony-stimulating factor which resulted in a sustained resolution of his neutropaenia.